Lactic Acid Fermentation of Arthrospira platensis (Spirulina) in a Vegetal Soybean Drink for Developing New Functional Lactose-Free Beverages - Niccolai, Alberto; Bažec, Kaja; Rodolfi, Liliana; Biondi, Natascia; Zlatić, Emil; Jamnik, Polona; Tredici, Mario R. (Frontiers in Microbiology, 2020)
The main objective of this study was to evaluate the suitability of Arthrospira platensis F&M-C256 (spirulina) biomass in a vegetal soybean drink or in water, as substrate for lactic acid fermentation by the probiotic bacterium Lactiplantibacillus plantarum ATCC 8014 (LAB8014) and to evaluate the fermented products in terms of bacteria content and organic acids content, biochemical composition, total phenolics, and phycocyanin content, in vitro digestibility, in vitro and in vivo antioxidant activity. After 72 h of fermentation, a bacterial concentration of about 10.5 log CFU mL−1 in the broths containing the soybean drink + spirulina + LAB8014 (SD+S+LAB8014) or water + spirulina + LAB8014 (W+S+LAB8014) was found. Lactic acid concentration reached similar values (about 1.7 g L-1) in the two broths, while a different acetic acid concentration between SD+S+LAB8014 and W+S+LAB8014 broths was observed (7.7 and 4.1 g L−1, respectively). A. platensis biomass was shown to be a suitable substrate for LAB8014 growth. After fermentation, both broths contained a high protein content (> 50%). In both broths, total phenolics, in vitro and in vivo antioxidant activity increased after fermentation (+35%, +20%, and +93% on average, respectively), while phycocyanin content decreased (-40% on average). Digestibility of W+S+LAB8014 broth statistically improved after fermentation. This study highlights the potential of A. platensis F&M-C256 biomass as a substrate for the production of new functional lactose-free beverages.